Usefulness of Dark Field Microscopy in the Epidemiological Study of Leptospirosis in Human Patients with Pyrexia - Saravanan, S.; Selvaraju , G. (Research Perspectives of Microbiology and Biotechnology Vol. 3, 2024)
The present retrospective study was carried out to assess the prevalence of leptospirosis and the associated risk factors in the epidemiology of the disease. Human leptospirosis is an anthropozoonoses. The disease is grossly underreported in India as diagnosis is often challenging due to its protean clinical manifestations in tropical countries and the lack of simple diagnostic measures for early detection and control of the infection. In India is still being underreported though it has gained extreme public health importance, because of huge livestock and rodent populations and poor sanitary conditions. Fresh serum samples from 1730 human cases of different age and occupational groups, and either sex, with PUO or manifesting signs suggestive of leptospirosis were received by the Leptospirosis Laboratory at the Department of Veterinary Epidemiology and Preventive Medicine, Veterinary College and Research Institute, Namakkal from various hospitals in and around Namakkal district of Tamil Nadu from June 2008 to May 2012. The study revealed a positivity of 51.7 % was observed and 85 % of the positive cases manifested a milder anicteric leptospirosis. High positivity was observed in truck drivers (65.8%), age group of <20 years (55.4%), males (54.0%) and north-east monsoon (53.2%). From the calculated relative risk (RR), a strong positive association could be observed between truck drivers and males with the occurrence of leptospirosis. A prompt epidemiological investigation in susceptible animal populations along with an unequivocal diagnosis of positives in humans exposed to the risk factors, in association with the periodical vaccination of susceptible animals and control of rodents, could possibly halt the emergence of the disease. The present study could identify the risk factors and a one health approach is required to create awareness among the public on zoonotic diseases including risk factors, and prevention and control measures.